STRATEGI KOMUNIKASI FBI BALI RADIO DALAM MENINGKATKAN PENDENGAR PROGRAM HI BALI - Milenia, Anastasia; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
There's 62 radio stations in Bali which makes the competition becomes very tight. FBI Bali Radio made its efforts to attract and increase the number of listeners in order to continue to compete in business of media. The purpose of this research was to examine the communication strategy of FBI Bali radio in increasing the number of listeners for the Hi Bali program. This research type is qualitative descriptive using data collection techniques in the form of interviews, observations, and document studies. The result of this research is that in implementing its communication strategy, FBI Bali Radio using the strategy of knowing the audience, Composing messages, Determining the methods such as  Redundancy, Canalizing, Informative, Persuasive, and Educational. Furthermore, in the context of media selection, apart from relying on on air and streaming, FBI Bali radio also uses social media Keywords:   FBI Bali radio, Communication Strategy, increasing listeners.